2012
DOI: 10.1111/j.1948-7134.2012.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of larval density, food stress, and parasitism on the bionomics of the dengue vector Aedes aegypti (Diptera: Culicidae): implications for integrated vector management

Abstract: New larval control strategies for integrated vector management of Aedes aegypti are in high demand, including the use of biological control agents. Exposure of Aedes aegypti to parasites, starvation, and overcrowded conditions during larval development reduces the probability of survival to eclosion, can directly affect fitness parameters such as adult size and fecundity, and can affect the size, provisioning, and viability of eggs produced by females. We compared these parameters after exposing larvae to 1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…aegypti and Ae. albopictus respectively) are comparable to those previously reported for these species (Mori , Reyes‐Villanueva and Rodriguez‐Perez , Farjana and Tuno , Mitchell‐Foster et al ) although mean number of eggs per female was lower than reported from two Ae. aegypti populations from Brazil (≈ 75, Madeira et al ).…”
Section: Discussionsupporting
confidence: 89%
“…aegypti and Ae. albopictus respectively) are comparable to those previously reported for these species (Mori , Reyes‐Villanueva and Rodriguez‐Perez , Farjana and Tuno , Mitchell‐Foster et al ) although mean number of eggs per female was lower than reported from two Ae. aegypti populations from Brazil (≈ 75, Madeira et al ).…”
Section: Discussionsupporting
confidence: 89%
“…Variables in the larval environment, such as: temperature, population density, nutritional availability, and the presence of toxins have been shown to have significant effects upon time of larval development, adult body size, nutritional stores, immunity, reproductive capability and most significantly vector capacity [ 23 - 32 ]. In studies by Mitchell-Foster [ 23 ] and Alto [ 23 ], Ae. aegypti and Culex pipiens larvae raised under reduced nutrient conditions had decreased adult size, reduced numbers of eggs and smaller egg size [ 23 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In studies by Mitchell-Foster [ 23 ] and Alto [ 23 ], Ae. aegypti and Culex pipiens larvae raised under reduced nutrient conditions had decreased adult size, reduced numbers of eggs and smaller egg size [ 23 , 26 ]. Other studies found the amount of food larvae were given affects the time spent in the pupal life stage [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serpa et al [109] varied number of individuals but decreased both food and volume as the number of individuals increased. Mitchell-Foster et al [110] and Price et al [87] also increased density and decreased food at the same time. While none of these investigations contradicts the results of my experiments, none of them can be used as direct support because their designs do not allow the possibility of an interaction between food and density.…”
Section: Discussionmentioning
confidence: 99%
“…Adult females require a blood meal to mature eggs. The size of the adult female is directly related to the size of the pupa and reflects the competitive success of the larva; large females take larger blood meals, mature more and larger eggs, and live longer than small females [1,4,18,23,35,58,70,81,83,84,86,104,110,129,186,187], but see [35], and may be more effective disease vectors [8891], but see [9297,188] although this is likely a result of their robustness rather than a direct result of size selection. Larger eggs hatch into larger larvae and start their lives with an advantage [54].…”
Section: Discussionmentioning
confidence: 99%